Informal carers' experiences and needs when supporting patients through chemotherapy: a mixed method study. (8th July 2013) - Ream, E.; Pedersen, V.H.; Oakley, C.; Richardson, A.; Taylor, C.; Verity, R.
Abstract : Informal carers provide important emotional support to patients having chemotherapy and assistance in monitoring and managing side‐effects. If they are inadequately supported in this, patient and carer morbidity may result. This study explored needs of informal carers supporting patients with cancer having chemotherapy. The study used a mixed methods approach. Carers of colorectal or lymphoma cancer patients at one comprehensive cancer centre participated. Questionnaire data informed semi‐structured interviews conducted with a subsample of respondents. Interviews were analysed using Framework analysis. Questionnaire data were analysed descriptively. Fifty‐nine informal carers were invited to participate; 48 returned the questionnaire (response rate 81%) and 13 were interviewed. Informal carers' needs for information about chemotherapy and its side‐effects were largely met although a third felt completely or somewhat unprepared to deal with particular symptoms experienced by patients at home. Many carers had unmet needs regarding financial support and their own needs as carers. Assertiveness was important to many caring roles, but it appeared difficult for informal carers to adopt when they were unsupported in this and their role was unrecognised by health professionals. Future research should develop interventions to systematically prepare carers for their carer role, improve carer involvement and ultimately improve patient outcomes.